2013
DOI: 10.1371/journal.pntd.0002271
|View full text |Cite
|
Sign up to set email alerts
|

Fertility, Gestation Outcome and Parasite Congenital Transmissibility in Mice Infected with TcI, TcII and TcVI Genotypes of Trypanosoma cruzi

Abstract: This work aims to compare the effects of acute or chronic infections with the T. cruzi genotypes TcI (X10 strain), TcII (Y strain) and TcVI (Tulahuen strain) on fertility, gestation, pup growth and the possible vertical transmission of parasites in BALB/c mice. The occurrence of congenital infection was evaluated by microscopic examination of blood and/or qPCR on blood and heart in newborn pups and/or older offspring submitted to cyclophosphamide-induced immunosuppression in order to detect possible cryptic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
3
27
0
1
Order By: Relevance
“…1). Similar results are observed in experimental infections, in which parasitemias in transmitting dams (acutely infected) are particularly high compared to nontransmitting animals (Cencig et al, 2013).…”
Section: Parasitemia During Pregnancy and Transmission Of Congenital supporting
confidence: 82%
See 2 more Smart Citations
“…1). Similar results are observed in experimental infections, in which parasitemias in transmitting dams (acutely infected) are particularly high compared to nontransmitting animals (Cencig et al, 2013).…”
Section: Parasitemia During Pregnancy and Transmission Of Congenital supporting
confidence: 82%
“…A recent work of our team studied congenital transmission from mouse dams acutely or chronically infected with the T. cruzi strains X10 (TcI), Y (TcII) and Tulahuen (TcVI). It showed that congenital infection (detected by blood microscopic examination in offspring submitted to cyclophosphamide-induced immunosuppression in order to activate possible cryptic infection) occurred in approximately 4% of living pups born to dams acutely infected with Y or Tulahuen strains, but not with X10 and not in those born to chronically infected animals (Cencig et al, 2013). So, mice and rats display lower yield of maternal-fetal parasite transmission than humans.…”
Section: Parasite Diversity and Congenital Transmission In Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Another study suggests that intrauterine growth retardation occurs during chronic murine T. cruzi infection, but it did not note any difference between other reproductive outcomes of infected and uninfected mice. 32,33 Studies in non-human primates have not observed differences in fertility, menstrual cycle parameters, or numbers of stillbirths or miscarriages between uninfected and infected females. 34 Congenital Chagas disease in humans has been associated with pre-term labor, low birth weight, and neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Según la Organización Mundial de la Salud (OMS), se estima que al menos dos millones de mujeres en edad fértil en América Latina están infectadas por T. cruzi y en fase crónica, con una incidencia de infección congénita de alrededor de 15.000 casos por año (9), y que en los países o regiones con mayor endemia puede haber más posibilidades de transmisión congénita (10). En los estudios en modelos animales se ha observado que los ratones infectados con el parásito T. cruzi durante la gestación, no ganan el mismo peso que los que no están infectados; además, la tasa de mortalidad de los recién nacidos de madres infectadas es mayor que en los de madres no infectadas (11).…”
unclassified